Code name, Johnny Walker : the extraordinary story of the Iraqi who risked everything to fight with the U.S. Navy SEALs /: the extraordinary story of the Iraqi who risked everything to fight with the U.S. Navy SEALs. ([2014]) - Walker, Johnny, 1964-; DeFelice, Jim, 1956-
No abstract available